Rancang Bangun Robot Line Follower Berbasis Arduino sebagai Media Edukasi pada Mata Kuliah Robotika - Hairil Novansyah; Sigit Candra Setya; Efan (BETRIK, 2025)
Information technology is currently growing rapidly, one of which is the use of a robot. This researcher aims to design and build a Line Follower robot as a demonstration medium in robotics courses at the Pagar Alam High School of Technology. Researchers make a robot for demonstration media in robotics courses, because in this course the conventional media still uses power points and a video. Therefore, it is necessary to make a tool for conventional media as a teaching aid in robotics courses. by utilizing a microcontroller, Motor Drive, PIR Sensor and DC Motor, to make a Line Follower robot. The method used in this research is the Rapid Application Development (RAD) system developer method. The stages used are Requirement planning, design workshop, Build The System and Implementation. The devices that the researchers use include the ATmega328 microcontroller, motor drive, DC motor, and infrared sensor. To obtain data in this study, researchers used data collection techniques including observation, interviews and literature study. From the results of the tests that have been carried out by researchers for line follower cars, researchers have succeeded in making and running a line follower car and this car will be shaped like an offroad car that runs automatically following the trajectory guide line. Based on the results of the pre-test, the average score was 35.9% and the post-test score was 90.9% in the high category. Based on the results of these tests, it can improve student learning systems before and after there is a tool as a medium of democracy in robotics courses.